World Bank East Asia and Pacific Economic Update, October 2021 : Long COVID - World Bank (Washington, DC: World Bank, 2021)
The East Asia and Pacific (EAP) region is suffering a reversal of fortune. In 2020, many EAP countries successfully contained COVID-19 and economic activity swiftly revived as other regions struggled with the pandemic and economic recession. Now the region is being hit hard by the COVID-19 Delta variant while many advanced economies are on the path to economic recovery. The disease is damaging the economy and is unlikely to disappear in the foreseeable future. In the near term, the persistence of the pandemic will prolong human and economic distress unless individuals and firms can adapt. In the longer term, COVID-19 will reduce growth and increase inequality unless the scars are remedied and the opportunities grasped. Policy action must help economic agents to adjust today and make choices that avert deceleration and disparity tomorrow.